PENGARUH ECONOMIC VALUE ADDED, UKURAN KOMITE AUDIT dan PROPORSI KOMISARIS INDEPENDEN TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Indeks LQ45 di BEI) - B31112104, Erma Wijayanti (Jurnal Manajemen Update, 2016)
EVA as an indicator of the company's financial performance complies with and supports the principles of the GCG. Maximization of the firm value is the company’s objective and obligation. However, there are problems in achieving this, one of which is triggered by the use of cash flow. This research aims to examine the effect of EVA and GCG on the firm value with free cash flow as control variable. The samples used in this research were 15 companies in the LQ45 index  companies listed on the stock exchange Indonesia for 5 years i.e. in 2010, 2011, 2012, 2013 and 2014. The sample were taken through purposive sampling. The analysis of data used a multiple regression test analysis tool which was preceded by the classic assumption test consisting of the normality test and heteroscedasticity test. The hypothesis was tested using F-test and t-test with a significance level α = 0.05. The result of individual parameter significance test were conducted through regression. The research findings showed that the EVA has a positive and significant effect on the PBV; the audit commitee had a negative and insignificant effect on the PBV ; the proportion of independent commissioners had a positive and insignificant effect on the firm value (PBV). Keywords: Economic Value Added, Good Comporate Governance,  Price Book Value, free cash flow.